RANCANG BANGUN ALAT PENGUKUR KONSENTRASI OKSIGEN (O2) BERBASIS IoT MIKROKONTROLLER ESP32 PADA VENTILATOR PURITAN BENNETT 840 - Satria Putra Nurhilal; Abdul Haris Haris Kuspranoto; Muhammad Ulin Nuha ABA (LPPM POLBITRADA, 2024)
IoT systems allow users to monitor and control devices remotely using a smartphone or other device connected to the internet. IoT systems can help improve efficiency, effectiveness, and security in a variety of applications. One of the uses of IoT systems in the field of Health is to combine IoT devices with medical sensors. This research integrates Internet of Things (IoT) technology with oom202 sensor to detect and regulate oxygen (O2) concentration in Puritan Bennett 840 ventilator, especially for baby head box in Perinatology room. The Sensor reads O2 levels, sends data to the ESP32 microcontroller, and displays the results in real-time on the LCD as well as the Android device. The system provides notification if O2 levels are beyond safe limits, with an average tool accuracy of less than 1% and a measurement error of only 0.18%, ensuring effective and precise O2 monitoring.